Study on taxpayers' awareness and confidence in administering self-assessment / Ho Juan Keng … [et al.] - Keng, Ho Juan; Sapari, Afidah; Othman, Rani Diana; Ern Chen, Loo (2006)
Regardless of the level of education and whether the respondents had received any formal education in taxation, most of them knew the differences between the Official Assessment System (OAS) and Self-Assessment System (SAS). The majority also knew that for individual taxpayers, OAS was replaced with SAS effective from 2004. Although they agreed that both the taxpayers and tax officers should be knowledgeable in assessing tax liabilities, the respondents still nevertheless would still preferred OAS to SAS. While they agreed that SAS would reduce tax administrative cost and would allow taxpayers the opportunities to manage their own tax affairs, they did not consider these as justifiable reasons for adopting SAS. Under the OAS, about 70% prepared and filed their own tax returns while under self-assessment, only about 40% did so, as the respondents were not confident of getting all aspects of self-assessment correct. They felt mentally very stressful for having to understand the tax laws and rulings, to keep up to date with the frequent changes to ensure that they were able to correctly file their tax returns, besides having to be subjected to post assessment reviews, with the possibility of being penalized for unintentionally committed errors. They were not confident that the tax authority would advise taxpayers regarding unintentionally committed errors, nor would the tax authority treat the community as honest taxpayers. They felt that the tax laws that allowed the IRS far more time (of six years) to review an assessment and the 30 days allowed to any taxpayer to appeal against an assessment as unfair and unjustified.